(untitled) (Revista Latino-Americana de Enfermagem, 2009)
Qualitative and phenomenological study based on reports of women between 48 and 55 years old with spontaneous menopause for 12 months or more. Results evidenced five theme categories that were analyzed and interpreted based on Maurice Merleau-Ponty's theoretical-philosophical reference framework. Among the categories that emerged from reports, the theme "reflecting on sexuality" was emphasized, and is presented with a view to understanding the existential aspects of the climacteric experience, focusing on the exercise of sexuality.